Associations between strength and power with throwing performance in high level male and female javelin throwers - Köykkä, M.; Ihalainen, J. K.; Saari, A.; Waller, B.; Cronin, N. J. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
This study investigated the associations between strength and power measures and estimated javelin throwing performance. Thirteen male (personal best: 77.0 ± 5.7 m) and thirteen female (55.8 ± 5.8 m) javelin throwers underwent various lower and upper body power and strength tests, along with a javelin throwing test. Associations with throwing performance were observed for lower body power measures in males and upper and lower body maximal strength in females, suggesting sex-specific differences in important physical characteristics for throwing.